Role of functional food with gut modulatory potential in atopic dermatitis - Lee, Ying Hui (Nanyang Technological University, 2024)
Atopic dermatitis (AD) is a common paediatric skin disease with no satisfactory therapy despite increasing prevalence of the disease. AD is characterized by dysbiosis of gut and skin microbiota. Emerging evidence indicates that manipulation of gut microbiota using functional foods including probiotics and prebiotics can alleviate the AD clinical symptoms. Prebiotics can rebalance the microbial communities by providing a nutrient-rich gut environment for the beneficial commensals to thrive, thus prebiotics supplementation is considered a promising approach for successful modulation of gut microbiota to prevent as well as to treat AD patients.